Magnetic resonance for radiotherapy management and treatment planning in prostatic carcinoma - Lim, Christopher (Br J Radiol, 2015)
MRI has an important role for radiotherapy (RT) treatment planning in prostate cancer (PCa) providing accurate visualization of the dominant intraprostatic lesion (DIL) and locoregional anatomy, assessment of local staging and depiction of implanted devices. MRI enables the radiation oncologist to optimize RT planning by better defining target tumour volumes (thereby increasing local tumour control), as well as decreasing morbidity (by minimizing the dose to adjacent normal structures). Using MRI, radiation oncologists can define the DIL for delivery of boost doses of RT using a variety of techniques including: stereotactic body radiotherapy, intensity-modulated radiotherapy, proton RT or brachytherapy to improve tumour control. Radiologists require a familiarity with the different RT methods used to treat PCa, as well as an understanding of the advantages and disadvantages of the various MR pulse sequences available for RT planning in order to provide an optimal multidisciplinary RT treatment approach to PCa. Understanding the expected post-RT appearance of the prostate and typical characteristics of local tumour recurrence is also important because MRI is rapidly becoming an integral component for diagnosis, image-guided histological sampling and treatment planning in the setting of biochemical failure after RT or surgery.